IMMU-05. DISRUPTION OF THE CCR2 CHEMOKINE RECEPTOR PATHWAY OVERCOMES THERAPEUTIC RESISTANCE TO PD-1 BLOCKADE IN MALIGNANT GLIOMA. (11th November 2019) - Flores-Toro, Joseph; Luo, Defang; Campbell, James; Charo, Israel; Singh, Rajinder; Schall, Thomas; Datta, Meenal; Jain, Rakesh; Mitchell, Duane; Harrison, Jeffrey
Abstract: INTRODUCTION: Large scale clinical trials have failed to determine efficacy of adjuvant PD-1 blockade in recurrent glioblastoma (GBM). However, recent phase 2 clinical trial results demonstrating the potential of neo-adjuvant anti-PD-1 treatment have renewed enthusiasm for the use of immune checkpoint inhibitors (ICIs) in GBM. Additional benefit of ICIs in GBM will likely derive from development of novel therapies directed against immunosuppressive resistance mechanisms. Chemokine receptor 2 (CCR2) expressing tumor infiltrative immune suppressive myeloid cells represent a targetable axis within ICI resistant gliomas. We have established that CCR2 disruption unmasks an effect of anti-PD-1 therapy in ICI resistant murine glioma models. However, the mechanism(s) by which combined inhibition of PD-1 and CCR2 achieves efficacy is unknown. OBJECTIVE: Determine the impact of combination anti-PD-1 and CCR2 antagonism on immune cells within anti-PD-1 resistant gliomas. METHODS: Immune cell characteristics were determined in CCR2 antagonist (CCX872)/anti-PD-1 treated KR158 or 005 GSC glioma-bearing wild type or CCR2 +/rfp /CX3CR1 +/gfp reporter mice. RESULTS: CCX872 increased median survival (32 vs. 50 days, P=.002) in KR158 tumor-bearing animals and in combination with anti-PD-1 significantly increased durable survival (P=.0005). In 005 GSC glioma-bearing mice, combination therapy also enhanced median survival (30 vs. 49 days, P=.005). CCX872 decreased CD45 + /CD11b hi /Ly6C hi MDSCs (40%, P=.038) within gliomas, and increased these cells within bone marrow in both models (74%, P=.020). Three distinct intra-tumoral populations of CCR2 + and CX3CR1 + cells were identified in both glioma models including CCR2 + /CX3CR1 - /CD45 hi /CD11b lo, CCR2 + /CX3CR1 + /CD45 hi /CD11b hi /Ly6C hi, and CX3CR1 + /CD45 lo /CD11b hi /F4/80 + /MHCII +, with both CCR2 + populations being reduced by CCX872 treatment. Examination of tumor infiltrating lymphocytes revealed both increased presence and decreased exhaustion (PD-1 + /Tim3 + ) of CD4 + (P=.029) and CD8 + (P=.011) T-cells following CCX872/anti-PD-1 treatment. CONCLUSION: CCX872/anti-PD-1 combination therapy is effective in clinically relevant murine glioma models, providing a basis to progress this novel combinatorial treatment to human clinical trials.